EFFICACY OF SODIUM NUCLEINATE INCOMPLEX TREATMENT OFPATIENTS WITH RECURRENT PYELONEPHRITIS - Stepanova, N.; Driyanska, V.; Kruglikov, V.; Lebid, L.; Kornilina, O.; Romanenko, O.; Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2014)
The aim of our study was to determine the effectiveness of Sodium nucleinate in treatment of patients with recurrent pyelonephritis. Material and methods. This clinical study is a prospective, open, controlled, randomized clinical study. Two types of therapies were evaluated in parallel groups. 98patients with recurrent pyelonephritis were examined in the dynamics of treatment. We investigated the state of the genitourinary system microbiota, mucosal immunity performance of the urogenital tract and contents of blood cytokines. After the examination the patients were divided by the applied therapeutic approach. The first group of the women (n=55) received antibiotic therapy and Sodium nucleinate 0.25 g 4 times per day for 2 weeks. The second group of the women (n=43) received only antibiotics. Results. The frequency of eradication of U. urealyticum (including in association with M. hominis) was significantly higher in patients of the first group. We have identified a significantly higher phagocytic activity and a phagocytosis intensity of neutrophils in samples from the vagina in women of the first group (46 [28-49] vs 17 [13-27.5] p = 0.002 and 3.19 [2.34-4.9] against 2.8 [1.23-3.6] p=0.02, respectively).The study of mucosal immunity has demonstrated a significant decrease the content of lactoferrin and increasing sIg A in the urine of patients of group (6.85 [0.2-80] vs 0 [0-0.4] ng/ml, p=0.01 and 0.42 [0-0,7] vs. 3.2 [0-3,7]g/ml, p=0.04, respectively).In addition, the use of Sodium nucleinate promoted to a significant reduction of high levels of all investigated cytokines: IL-4 (p=0.003), IL-17 (p=0.005), NGAL (p=0.02), TNF- (p=0.02) and MCP-1 (p=0.03). In the control group was achieved just the reduction in levels of IL-4 (p=0.007) and IL-17 (p=0.04). Conclusions. Thus, the application of the proposed therapies can improve the effectiveness of the treatment of patients with recurrent pyelonephritis by normalization of mucosal immunity of the genitourinary system and the cytokine profile. We believe that the traditional antibiotic therapy ofpatients with recurrent pyelonephritis advisable to supplement of Sodium nucleinate at a dose of 0.25g 4 times / day for 2 weeks.